2020
DOI: 10.1038/s41586-020-2396-4
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic pathway for bile acid dehydroxylation by the gut microbiome

Abstract: The gut microbiota synthesize hundreds of molecules, many of which are known to impact host physiology. Among the most abundant metabolites are the secondary bile acids deoxycholic acid (DCA) and lithocholic acid (LCA), which accumulate at ~500 µM and are known to block C. difficile growth 1 , promote hepatocellular carcinoma 2 , and modulate host metabolism via the GPCR TGR5 3 . More broadly, DCA, LCA and their derivatives are a major component of the recirculating bile acid pool 4 ; the size and composition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
309
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 365 publications
(319 citation statements)
references
References 46 publications
10
309
0
Order By: Relevance
“…Lower bile acid concentration probably influences the composition of the microbiota and hence may increase bile acid dehydroxylation. (40) Variants of PPP1R3B have not been associated with gallstones. (41) Intriguingly, our preliminary data with limited number of subjects with gallstone disease data available showed that 2 out of 25 (8%) subjects with genotype AA had gallstones compared to 5 out of 15 (33%) with genotype AG (P = 0.021).…”
Section: Discussionmentioning
confidence: 97%
“…Lower bile acid concentration probably influences the composition of the microbiota and hence may increase bile acid dehydroxylation. (40) Variants of PPP1R3B have not been associated with gallstones. (41) Intriguingly, our preliminary data with limited number of subjects with gallstone disease data available showed that 2 out of 25 (8%) subjects with genotype AA had gallstones compared to 5 out of 15 (33%) with genotype AG (P = 0.021).…”
Section: Discussionmentioning
confidence: 97%
“…a-diversities were calculated using Shannon index and b-diversity was calculated using Bray-Curtis dissimilarity based on relative abundances at species levels (Vegan package in R). The non-redundant gene catalogue was queried using USEARCH ublast 53 with proteins in the bai operon of C. scindens 26 or proteins in the bacterial isolates reported here as 5AR, 5BR, 3bHSDH I, or 3bHSDH II to identify and annotate homologous proteins with at least 40% identity and 80% coverage to the query sequence. An identical processing pipeline has been applied to the dataset describing the gut microbiome in Sardinian centenarians 8 .…”
Section: Human Sample Collectionmentioning
confidence: 99%
“…Serum bile acids (BAs), as important signaling molecules, participate in the regulation of BA metabolism and the activation of several kinds of bile acid receptors [25]. Most BAs come from reabsorption in the intestinal epithelium after being processed by gut microbes and then entering the enterohepatic circulation [26,27]. Therefore, we measured total bile acid (TBA) and the composition of BAs in serum to examine differences induced by LR and LP treatment.…”
Section: Lr and Lp Treatments Reduced Ld-induced Gallstones And Metabmentioning
confidence: 99%